Domain structure of volcanics’ ferromagnetic grains: A case study of the Saatly ultradeep well, Azerbaijan - Novruzov, Z.A. (Геофизический журнал, 2019)
Various magnetic properties of magnetic minerals show strong grain-size depen-dence. This dependency occurs because these parameters are influenced by the magnetic grain-size (domain state) of the samples. Natural rocks often contain a mixture of different magnetic minerals with different grain-size (domain states). Thus determination of the domain state is important. The Saatly ultradeep well’s volcanics were used as a research material. In the depth intervals of 3540—8126 m the volcanics had been revealed by the borehole. Магнитные свойства различных магнитных минералов очень зависят от размера зерен (доменного состояния). Горные породы часто содержат смесь различных магнитных минералов с различными размерами зерен (доменных состояний). В качестве материала для определения доменного состояния зерен минералов использовано вулканиты с сверхглубокой скважины Саатлы в интервале глубин 3540-8126 м. Магнітні властивості різних магнітних мінералів дуже залежать від розміру зерен (доменного стану). Гірські породи часто містять суміш різних магнітних мінералів з різними розмірами зерен (доменних станів). Як матеріал для визначення доменного стану зерен мінералів використано вулканіти з надглибокої свердловини Саатлі в інтервалі глибин 3540—8126 м.